An optical sensor for dengue envelope proteins using Polyamidoamine Dendrimer biopolymer-based nanocomposite thin film: enhanced sensitivity, selectivity, and recovery studies - Omar, Nur Alia Sheh; Yap, Wing Fen; Ramli, Irmawati; Sadrolhosseini, Amir Reza; Abdullah, Jaafar; Yusof, Nor Azah; Mustapha Kamil, Yasmin; Mahdi, Mohd Adzir (Multidisciplinary Digital Publishing Institute, 2021)
This paper proposes a novel idea to enhance the sensitivity and selectivity of surface plasmon resonance (SPR) optical sensor for detection of dengue virus type-2 envelope proteins (DENV-2 E-proteins) using polyamidoamine (PAMAM) dendrimer biopolymer-based nanocomposite thin film. For this purpose, two ranges of DENV-2 E-protein concentrations, i.e., 0.000008–0.0001 nM and 0.00008–0.005 nM were evaluated, and the lowest detectable concentration was achieved at 0.00008 nM. The incorporation of PAMAM dendrimer-based nanocomposite thin film with an SPR sensor exhibited a significant increase in sensitivity and binding affinity to a lower range DENV-2 E-protein concentrations. Moreover, the proposed sensor displayed good selectivity towards DENV-2 E-proteins and have an average recovery of 80–120%. The findings of this study demonstrated that PAMAM dendrimer-based nanocomposite thin film combined with SPR sensor is a promising diagnostic tool for sensitive and selective detection of DENV-2 E-proteins.